2000
DOI: 10.1046/j.1365-8711.2000.03106.x
|View full text |Cite
|
Sign up to set email alerts
|

The 0.1-100 keV spectrum and variability of Mrk 421 in a high state

Abstract: The results of a BeppoSAX target of opportunity (TOO) observation of the BL Lac object Mrk 421 during a high‐intensity state are reported and compared with monitoring X‐ray data collected with the BeppoSAX Wide Field Cameras (WFC) and the RXTE All Sky Monitor (ASM). The 0.1–100 keV spectrum of Mrk 421 shows continuous convex curvature that can be interpreted as the high‐energy end of the synchrotron emission. The source shows significant short‐term temporal and spectral variability, which can be interpreted in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…We observed and detected Mkn 421 with the INTEGRAL instruments IBIS/ISGRI, JEM-X and OMC during a high state that followed the detection of a powerful TeV energy outburst (Cortina & Holder 2013) that was likely subsiding during our observation. The X-ray flux is among the highest previously recorded for this object by INTEGRAL itself and other satellites (Malizia et al 2000;Donnarumma et al 2009;Abdo et al 2011). The optical state is also very bright, with few precedents (Tosti et al 1998).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We observed and detected Mkn 421 with the INTEGRAL instruments IBIS/ISGRI, JEM-X and OMC during a high state that followed the detection of a powerful TeV energy outburst (Cortina & Holder 2013) that was likely subsiding during our observation. The X-ray flux is among the highest previously recorded for this object by INTEGRAL itself and other satellites (Malizia et al 2000;Donnarumma et al 2009;Abdo et al 2011). The optical state is also very bright, with few precedents (Tosti et al 1998).…”
Section: Discussionmentioning
confidence: 69%
“…This synchrotron self-Compton component peaks at very high energies, making this blazar a strong TeV emitter, although the TeV spectrum is often heavily suppressed by the Klein-Nishina effect (Maraschi et al 1999;Fossati et al 2008;Mankuzhiyil et al 2011). Mkn 421 was the target of many multiwavelength campaigns involving high energy satellites, Cherenkov telescopes and ground-based optical and radio facilities (Takahashi et al 1996;Maraschi et al 1999;Malizia et al 2000;Fossati et al 2000a,b;Brinkmann et al 2001;Albert et al 2007a;Lichti et al 2008;Fossati et al 2008;Donnarumma et al 2009;Acciari et al 2009;Ushio et al 2009;Tramacere et al 2009;Horan et al 2009;Aleksić et al 2010;Isobe et al 2010;Abdo et al 2011;Acciari et al 2011;Barres de Almeida 2011;Aleksić et al 2012;Shukla et al 2012). The variations at X-ray and TeV frequencies are often very well correlated with no measurable delay (Maraschi et al 1999), but complex intra-day X-ray variability is present (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…3 and 4 in Kirk et al 1998). The loop path has been frequently reported in X-rays (e.g., Sembay et al 1993;Takahashi et al 1996;Kataoka et al 1999;Zhang et al 1999Zhang et al , 2002Malizia et al 2000;Ravasio et al 2004) and, in one case, in the infrared (Gear et al 1986). In the optical regime, Xilouris et al (2006) have reported a similar pattern, and Wu et al (2007a) showed a clockwise loop with the nightly means of magnitudes and colors.…”
Section: Color Evolution During Flaresmentioning
confidence: 74%
“…In other regime like gamma-ray and X-ray, the loop path has been reported frequently (e.g. Sembay et al 1993;Takahashi et al 1996;Malizia et al 2000;Albani et al 2007;Kataoka et al 2010;Zhang et al 1999;Zhang et al 2002).…”
Section: Color Behavior and Spectral Hysteresismentioning
confidence: 99%